Modelo de vivienda rural sostenible en el sector vereda el verjón - Piñeros Tovar, Harold Santiago (Universidad Antonio Nariño, 2024)
The sustainable rural housing project in the paramo focuses on the design and construction of homes adapted to the unique and challenging conditions of high mountain ecosystems. These homes aim to minimize environmental impact and improve the quality of life for local communities through the use of eco-friendly technologies and materials.